(untitled) (International Journal of Engineering and Computer Science, 2018)
Publish/Subscribe (pub/sub) system is an emerging communication paradigm that offers efficient and decoupled information dissemination in distributed environments. Decoupling increases the privacy of each participants in the system . Publishers generate the flow of information as publications of interests expressed as subscriptions. The perfect decoupling is maintained by using the pairing based cryptographic mechanisms. The provisioning of basic security mechanisms such as authentication, confidentiality, access control are highly challenging in a content based publish/subscribe system. This work proposes a novel approach to provide confidentiality , authentication and access control in a brokerless content based publish/subscribe system using Hierarchical CP -ABE (Ciphertext Policy Attribute Based Encryption) scheme. So the new Publish/Subscribe system is very efficient with less computational time for cryptographic operations and also provide fine grained access control hierarchically.